Causes for hospitalization of elderly individuals due to primary care sensitive conditions and its associated contextual factors - Soares,Angela Maria de Medeiros (2019)
SUMMARY OBJECTIVE The objective of this study was to analyze the hospitalizations of the elderly for conditions sensitive to primary care (ICSAP) and associated contextual factors, referring to elderly people aged 60 and over, living in municipalities in the Northeast region. METHODS Characterized as being an ecological study using data from the Hospital Information System (SIH) and the Basic Attention Information System (SIAB) referring to elderly people aged 60 and over. RESULTS The total hospitalization rate was 527,524, with the highest number due to heart failure, followed by cerebrovascular diseases, and infectious gastroenteritis. Analyzing the ICSAP rates with the contextual factors, all were significant. Regarding the coverage of basic care, a similarity occurred between them, and for the rate of the number of consultations among the elderly, despite the greater number of these in the municipalities with higher hospitalization rates, there was no significant difference between them. CONCLUSION We conclude that the contextual factors interfere in the conditions of this hospitalization, necessitating, besides the improvement of primary care, an improvement in the living conditions of the elderly population.